Saints hommes de Chiraz et du Fārs: pouvoir, société et lieux de sacralité (Xe-XVe s.) - Aigle, Denise (Iran studies, 2023)
"In Saints hommes de Chiraz et du Fārs. Pouvoir, société et lieux de sacralité (Xe-XVe s.), Denise Aigle studies the spiritual role, but also the political one, played by the Sufi shaykhs. From the tenth century, Fārs was a a land of holiness with Shaykh Kabīr in Shiraz and Murshid al-Dīn Abū Isḥāq in Kāzarūn. This research is based on hagiographic sources, historical chronicles, literary sources and archival documents. The author shows how the pre-Islamic history of Fārs was integrated into spiritual Islam thanks to the mystical speculations of the Sufi shaykhs. The particular interest of this research is its contribution to the history of Lāristān, a region that has long remained terra incognita. Thanks to handwritten hagiographic documents preserved in several private libraries, we discover the existence and the role of spiritual masters until now totally unknown"--